Rapid eye movement sleep behavior disorder and potassium channel antibody-associated limbic encephalitis. - Iranzo, A; Graus, F; Clover, L; Morera, J; Bruna, J; Vilar, C; Martínez-Rodriguez, J; Vincent, A; Santamaría, J (2006)
Of six patients registered in our center with nonparaneoplastic limbic encephalitis associated with antibodies to voltage-gated potassium channels, the five men had rapid eye movement sleep behavior disorder (RBD) coincident with voltage-gated potassium channel antibody-associated limbic encephalitis onset. In three patients, immunosuppression resulted in resolution of RBD in parallel with remission of the limbic syndrome. RBD persisted in two patients with partial resolution of the limbic syndrome. Our findings suggest that RBD is frequent in the setting of voltage-gated potassium channel antibody-associated limbic encephalitis and can be related to autoimmune-mediated mechanisms. In addition, these observations suggest that impairment of the limbic system may play a role in the pathogenesis of RBD.